2011
DOI: 10.1152/ajpcell.00263.2010
|View full text |Cite
|
Sign up to set email alerts
|

Anion exchanger 1b, but not sodium-bicarbonate cotransporter 1b, plays a role in transport functions of zebrafish H+-ATPase-rich cells

Abstract: ϩ -ATPase rich (HR) cells in zebrafish skin and gills are also responsible for Na ϩ uptake and acid secretion functions. However, the basolateral transport pathways in HR cells are still unclear. In the present study, we tested the hypothesis if there are specific slc4 members involved in basolateral ion transport pathways in HR cells. Fourteen isoforms were identified in the zebrafish(z) slc4 family, and the full-length cDNAs of two novel isoforms, zslc4a1b (anion exchanger, zAE1b) and zslc4a4b (Na ϩ /HCO 3 Ϫ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 46 publications
5
92
0
Order By: Relevance
“…Due to the lack of sequence information the existence and role of anion exchangers (e.g. AE1) which were demonstrated to contribute to acid-base homeostasis in teleosts [46] remains unexplored for cephalopods.…”
Section: Branchial Acid-base Regulatory Machinerymentioning
confidence: 99%
“…Due to the lack of sequence information the existence and role of anion exchangers (e.g. AE1) which were demonstrated to contribute to acid-base homeostasis in teleosts [46] remains unexplored for cephalopods.…”
Section: Branchial Acid-base Regulatory Machinerymentioning
confidence: 99%
“…Knockdown of ERRa decreased the expression of metabolic genes (electronic supplementary material, figure S2) as well as the transporter genes related to H þ secretion (figure 4). Zebrafish HR cells express a set of transporters, including H þ -ATPase [26], NHE3b [49] and AE1 [30], that are critical for H þ secretion of HR cells; knockdown or inhibition of these transporters has been demonstrated to impair H þ secretion in zebrafish embryos [27,29,30]. In this study, it is shown that the decrease in H þ secretion caused by ERRa knockdown (figure 3a) was accompanied by a significant reduction in gene expression of these three transporters (figure 4), suggesting the actions of ERRa on H þ secretion can be attributed to the impairment of transporter expression.…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether ERRa regulates H þ secretion through affecting the expression of related transporters, we used Q-PCR to measure the expression of genes encoding transporters related to H þ secretion. While the majority of H þ secretion in HR cells is mediated by H þ -ATPase [29], the sodium hydrogen exchanger 3b (NHE3b) and anion exchanger 1b (AE1b) are also involved, as evidenced by observations that inhibition or knockdown of these transporters impaired H þ secretion [27,30]. As compared with the control group, the expression levels of apt6v1a (a subunit of H þ -ATPase) (figure 4a), slc9a3.2 (nhe3b) (figure 4b) and slc4a1b (ae1b) (figure 4c) were all significantly downregulated (e) Reduced HR cell number at yolk-sac skin in ERRa morphants…”
Section: (D) Decreased Expression Of H þ -Secreting-related Transportmentioning
confidence: 99%
“…12,13 In vertebrate systems the basolateral import of HCO 3 ¡ is achieved by various transporters of the SLC4 family, including anion exchangers, and Na C /HCO 3 ¡ co-transporters. 96,97 Two potential candidates for the transport of HCO 3 ¡ ions including an electrogenic Na C /HCO 3 ¡ co-transporter (NBC e ) and a Na C -dependent Cl ¡ /HCO 3 ¡ exchanger (NDCBE) were cloned from the squid giant axon. 98,99 While NDCBE had comparatively low transcript abundance in branchial epithelia but higher RNA levels in neurons, the electrogenic NBC was highly expressed in gill epithelia and expression of this gene was stimulated upon hypercapnic exposure.…”
Section: The Ph Regulatory Machinerymentioning
confidence: 99%